MOL1 is required for cambium homeostasis in Arabidopsis - Gursanscky, Nial Rau; Greb, Thomas (The plant journal, 2016)
Plants maintain pools of pluripotent stem cells which allow them to constantly produce new tissues and organs. Stem cell homeostasis in shoot and root tips depends on negative regulation by ligand-receptor...
Gesehen am 17.02.2017